Pustakawan sebagai komunikator dalam layanan referensi perpustakaan - Mr Syukrinur (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
This article discusses about the This article is titled librarian as a communicator in library reference service. The goal is to provide a description of how librarians as communicators communicate effectively in reference services and provide a library image in the eyes of the user. Characteristics of librarian as communicator studied in this paper. In addition, how the librarian's ability to communicate in reference services is also the focus of this study.Keywords: Librarian, communicator, reference service